Effect of social competence and school stress on bullying behavior in adolescent - Indri Eldiorita; Layyinah Layyinah (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2016)
This research aim to know the cause of bullying increasing, Based on research data that was collected from one of high schools in Jakarta which was found that many student who want to do bullying their friends and there were also many student become a victim of bullying by their own friends. This situation occur to show their exsistance in the school. Based on the previous study, there are many factors that influence bullying behavior, such social competence and school stress. Social competence is regarded as one of the most important protective factors in the prevention of behavioural problems, such bullying behavior (Gundersen, 2010). Besides that, high school stress have positively influence concerning to bullying (Karatzias, Power, Flemming, Lennan & Swanson, 2010).Samples amount in this research is students from first, second, and third degree of senior high schools ini Jakarta, academic year 2016/2017. Sampling technique in this study was nonprobability sampling with 205 respondents. This study used quantitative approach with linear regression as analysis method.Finding : from this study explains that social competence, such cooperative, emphaty and self control and school stress, such teacher interaction influence significantly on bullying behavior on adolescence. It is accordance with the finding of previous studies conducted by Bauman dan Del Rio (dalam Swearer dan Hymel, 2015) dan Irshar dan Atta (2013) that social competence and school stress influence on bullying behavior.